Penyalahgunaan serta Proses Penyelesaian Visa Kunjungan oleh Warga Negara Asing - Dicky Agustinus Sitanggang; Muhari Agus Santoso; Yusuf Eko Nahuddin; Raditya Feda Rifandana (University of Merdeka Malang, 2022)
This research is related to the process of resolving the misuse of visas carried out by foreign nationals in Indonesia. The purpose of this study is to find out the Process for the Settlement of Misuse of Visit Visas Performed by Indonesian Citizens in the implementation of the Settlement of Misuse of Visit Visas that have been carried out by Foreign Citizens, hereby implementing and providing the right impact on Foreign Citizens. The method of collecting data is directly conducting interviews with informants related to the completion process of Visit Visa Abuse. The method used is using empirical research methods with the transformation process of research data sourced from directly related informants. In this case, there is the implementation of the Visit Visa Abuse Settlement Process carried out by Foreign Citizens, there are still several obstacles and shortcomings, both in terms of supervision and the role of Immigration office employees in Indonesia.